Do Early Childhood Educators Benefit from a Playful Working Environment? A Study on Workplace Fun and Work Engagement - Jialing Yang; Xinghua Wang; Huifang Hong (Behavioral Sciences, 2025)
This study investigated early childhood education (ECE) teachers’ workplace fun and its relationship with their psychological capital and work engagement, both of which are crucial elements in improving their work efficiency. The relationship was investigated using quantitative methodology. Hypotheses and conceptual models were tested by structural equation modeling (SEM) on the raw data from 196 full-time ECE teachers via questionnaire surveys that investigated ECE teachers’ experiences of four aspects of workplace fun (i.e., formal fun activities, supportive practices for fun, coworker socializing, and fun job responsibilities). It was revealed that fun job responsibilities positively predicted the work engagement of ECE teachers. Furthermore, supportive practices for fun at ECE centers can indirectly predict the work engagement of teachers via the mediating effect of psychological capital. Based on the findings of this study, suggestions are provided to enhance teachers’ work engagement, including implementing supportive practices for fun by organizational management and promoting enjoyment in teachers’ job responsibilities.